1993
DOI: 10.1007/bf00199452
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical description of the stimuli to the lateral line system of fish, derived from a three-dimensional flow field analysis. III. The case of an oscillating sphere near the fish

Abstract: Abstract. The three-dimensional potential flow field of an oscillating sphere near a fish with an axially symmetric body was investigated mathematically. The spatial distributions of the stimuli to the lateral line system are derived from the flow-field analysis, taking into consideration the hydrodynamical interaction between the fish body and the flow of the oscillating sphere. This was done dependent on the location and the direction of oscillation of the sphere relative to the fish. The theoretical results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Satou et al demonstrated that the lateral line is involved in intersexual communication in the himé salmon (Oncorhynchus nerka) by showing that a spawning response was induced by a sphere vibrating at 21·Hz (Satou et al, 1994). The effect of the presence of the fish in distorting a dipole field has been investigated both theoretically (Hassan, 1993) and experimentally (Coombs et al, 1996), and it was shown to result in somewhat higher amplitudes but with minimal effect on the spatial characteristics of excitation patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satou et al demonstrated that the lateral line is involved in intersexual communication in the himé salmon (Oncorhynchus nerka) by showing that a spawning response was induced by a sphere vibrating at 21·Hz (Satou et al, 1994). The effect of the presence of the fish in distorting a dipole field has been investigated both theoretically (Hassan, 1993) and experimentally (Coombs et al, 1996), and it was shown to result in somewhat higher amplitudes but with minimal effect on the spatial characteristics of excitation patterns.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a limited number of investigations have been performed to understand how the information on distance of a vibrating source is represented in the overall excitation pattern along an array of neuromasts in the lateral line canal (e.g. Denton and Gray, 1982;Denton and Gray, 1983;Hassan, 1993;Coombs et al, 1996;Coombs and Conley, 1997a;Coombs and Conley, 1997b). A precise description, together with a quantitative interpretation, of such measured patterns that allows a reconstruction of the location and vibration direction of vibrating sources to be made is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A constant flow velocity of the stimulus is obtained by progressively reducing the amplitude of vibration, as vibration frequency is increased. Hassan (1993) showed that the flow, generated by a vibrating sphere near the cast model of a blind fish has characteristic patterns that can be detected by distributed SN, provided the (potentially strong) effects of the boundary layer are accounted for; and by distributed CN if the effect of the orientation of the canal relative to the position of the sphere has been accounted for. Curcic-Blake (2006) used a teflon sphere with 5 mm diameter vibrating in a direction roughly parallel to a ruffe lateral line canal, 10 cm in length, at a frequency around 70 Hz, placed at distances of the order of 10 mm.…”
Section: Tracking Swimming Fishmentioning
confidence: 99%
“…This slip flow velocity was taken as the stimulus to the SNs, with the assumption that the cupular lengths were long enough to penetrate the viscous boundary layer along the fish's skin. More sophisticated potential flow solutions have been developed to calculate the slip flow velocity distribution (and pressure distribution) over idealized fish body geometry (Hassan, 1985;Hassan, 1992a;Hassan, 1992b;Hassan, 1993). All of these studies ignore the fact that the real flow has to satisfy the no-slip boundary condition at the fish skin due to viscosity, i.e.…”
Section: Introductionmentioning
confidence: 99%